ANALYSIS OF THE CALCULATION AND REPORTING OF CORPORATE INCOME TAX 25 AT PT. NUSA CIPTA SOLUSI - Nindya Widya Putri; Erion Erion (International Research of Multidisciplinary Analysis, 2023)
This article was made to determine the analysis of the calculation of PPH Agency 25 conducted by PT. Nusa Cipta Solusi by Law no. 36 of 2008. Using primary data, researchers take the data through the accounting department in the form of company financial statements including balance sheets, commercial income statements, fiscal income statements, and The 2020 Tax Year Annual Tax Return. Data collection techniques by collecting documents related to the research being carried out in 2020. The analytical method used is descriptive quantitative method. Based on the research conducted by the author, the conclusion is that PT. Nusa Cipta Solusi has done well and correctly in calculating and reporting Corporate Income Tax 25, is by Law no. 36 of 2008, and has followed the Regulation of the Director General of Taxation on rate changes for the 2020 tax period